2023
DOI: 10.1021/acsmedchemlett.2c00481
|View full text |Cite
|
Sign up to set email alerts
|

Selective Wee1 Inhibitors Led to Antitumor Activity In Vitro and Correlated with Myelosuppression

Abstract: Wee1 is a tyrosine kinase that is highly expressed in several cancer types. Wee1 inhibition can lead to suppression of tumor cell proliferation and sensitization of cells to the effects of DNA-damaging agents. AZD1775 is a nonselective Wee1 inhibitor for which myelosuppression has been observed as a dose-limiting toxicity. We have applied structure-based drug design (SBDD) to rapidly generate highly selective Wee1 inhibitors that demonstrate better selectivity than AZD1775 against PLK1, which is known to cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Cyclic alkenes ( 67a ) retained WEE1 activity while improving selectivity against PLK1. Other unsaturated and saturated groups displayed decreased WEE1 activity . Furthermore, this study determined myelosuppression as an on-target consequence (independent of PLK1 inhibition) of WEE1 inhibition using the Colony forming unit-megakaryocyte assay (CFU-Mk) .…”
Section: Small Molecule Inhibitors Of Wee1 Kinasementioning
confidence: 99%
See 3 more Smart Citations
“…Cyclic alkenes ( 67a ) retained WEE1 activity while improving selectivity against PLK1. Other unsaturated and saturated groups displayed decreased WEE1 activity . Furthermore, this study determined myelosuppression as an on-target consequence (independent of PLK1 inhibition) of WEE1 inhibition using the Colony forming unit-megakaryocyte assay (CFU-Mk) .…”
Section: Small Molecule Inhibitors Of Wee1 Kinasementioning
confidence: 99%
“…Excruciating grade 4 or 3 myelosuppression is observed in almost all trials, limiting AZD1775’s potential as an ideal candidate . Initially, the toxicity profile of AZD1775 was inseparable from its off-target activity against PLK1, but recent studies and trials using more selective analogue ZN-c3 also showed treatment-related adverse events, including all grades of GI toxicities, ≥ grade 3 neutropenia, and other hematological toxicities. , Additionally, a 2023 study to optimize selective AZD1775 analogues identified thrombocytopenia as an inevitable consequence of WEE1 inhibition and not PLK inhibition, asserting thrombocytopenia as an on-target toxicity . On the other hand, IMP7068 exhibited negligible DLTs and treatment-related adverse events (TRAEs), including grade 1/2 increased levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and grade 1/2 diarrhea, which are tolerable .…”
Section: Adverse Events Of Existing Clinical Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The tyrosine kinase WEE1 is highly homologous to MYT1 and regulates the activity of both CDK1 and CDK2 through Tyr15-phosphorylation of CDK1, thereby controlling intra-S, G2/M, and M phase checkpoints. WEE1 inhibitors have been reported to exhibit an on-target thrombocytopenia effect, and the most advanced WEE1 inhibitor, AZD1775 , was suspended in phase 2 clinical trials due to dose-limiting toxicity caused by myelosuppression. As WEE1 is ubiquitously expressed in somatic cells and MYT1 expression is low in healthy cells and was only found elevated in paired acute myeloid leukemia and testicular germ cell tumors, limiting off-target inhibition of WEE1 is critically important in the design of novel MYT1 inhibitors …”
Section: Introductionmentioning
confidence: 99%